2003
DOI: 10.1002/ca.10147
|View full text |Cite
|
Sign up to set email alerts
|

Interphalangeal sesamoid bones of the great toe: An anatomic variant demanding careful scrutiny of radiographs

Abstract: We describe a patient who was found to have two sesamoid bones at the interphalangeal joint of the right great toe after radiographs for dislocation of the joint. Recognition of the sesamoids required careful scrutiny of the films. Interphalangeal sesamoids may cause painful callosities plantar to the joint or may become incarcerated in a dislocated joint. Our patient made a good recovery. The presence of sesamoid bones on the medial and lateral sides of the joint was unusual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In a cadaveric study of Japanese subjects, the prevalence was 96% in dissected specimens compared to 91% seen on radiographs (Masaki, 1984), probably reflecting the relative radiolucency of small bones or their composition of cartilage. In addition to this, Davies et al (2003) suggested a possible racial link between differences in IPJ ossicle prevalence because most of the literature regarding trauma to these ossicles is Japanese (Masaki, 1984;Miki et al, 1988;Yasuda et al, 1990). We report the prevalence of IPJ nodules in 40 British Caucasian cadavers, a group for whom the prevalence has not been determined.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a cadaveric study of Japanese subjects, the prevalence was 96% in dissected specimens compared to 91% seen on radiographs (Masaki, 1984), probably reflecting the relative radiolucency of small bones or their composition of cartilage. In addition to this, Davies et al (2003) suggested a possible racial link between differences in IPJ ossicle prevalence because most of the literature regarding trauma to these ossicles is Japanese (Masaki, 1984;Miki et al, 1988;Yasuda et al, 1990). We report the prevalence of IPJ nodules in 40 British Caucasian cadavers, a group for whom the prevalence has not been determined.…”
Section: Discussionmentioning
confidence: 83%
“…Previous work from our hospital (Davies et al, 2003) documented pathology from hitherto undescribed paired ossicles. Clearly, the results of the present study demonstrate that two accessory ossicles occur in a substantial proportion of the British Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…The hallucal IP sesamoid has a detrimental effect on the biomechanical functions of the first MTP and hallucal IP joints (Roukis and Hurless, 1997). IP sesamoids may cause painful callosities plantar to the joint or may become incarcerated in a dislocated joint (Davies et al, 2003). The reported frequency for hallucal IP sesamoid varies greatly in Caucasians from 5% (Bizarro, 1921) to as much as 50.6% (Pfitzner, 1892).…”
Section: Sesamoid Bones In Digits Of the Feetmentioning
confidence: 99%
“…According to anatomical studies, a single sesamoid at the hallucal IP joint is present in 52.5% of adults, with a paired sesamoid identified in a further 20% of adults for an overall prevalence rate of 72.5% [21]. We did not identify a case of two sesamoid bones at the hallucal IP joint, and identified only one reported case of this rare finding in the literature [23].…”
Section: Prevalence Of Sesamoids At the Hallucal Mtp And Ip Jointsmentioning
confidence: 81%